Developing a framework for assessing teaching effectiveness in higher education - Miguel, C.V.; Moreira, C.; Alves, M.A.; Campos, J.B.L.M.; Glassey, J.; Schaer, E.; Kockmann, N.; Porjazoska Kujundziski, A.; Polakovic, M.; Madeira, L.M. (Education for chemical engineers, 2019)
•A framework was established for assessing teaching effectiveness.•All stakeholders including employers contributed for the framework development.•Exploitation was carried out in different disciplines and European universities.•A toolkit was made available for testing by other higher education institutions. Evaluating the effectiveness of teaching and learning core knowledge outcomes and professional skills is a highly challenging task that has not yet been satisfactorily addressed at higher education level. The iTeach European project consortium developed a framework for assessing the effectiveness of various pedagogical methodologies in chemical engineering education, including those aiming to promote important core competencies related to employability, in a range of geographical and educational contexts. The framework was firstly implemented in a core chemical engineering area (reaction engineering) to check its usability and robustness, and subsequently was also tested on a range of subject areas from various branches of engineering and other disciplines, one of which is analysed in more detail in this contribution. The results of this broader assessment encompassed a much more diverse student body with varying educational experiences and a wider range of different teaching methodologies. The outcomes of this assessment are highlighted and the benefits of such an objective approach for evaluating teaching effectiveness is discussed.